Differences between Trainee Integrative Psychotherapists and Professional Psychotherapists in relation to their LGB Client's Competencies/MSc Integrative Counselling and Psychotherapy: Individual Research Project - Apostolopoulou Aggeliki (2019)
Introduction, History of Homosexuality, Homosexuality and Homophobia, Homosexuality and Mental Health, Gay Affirmative Therapy, Cognitive-Behavioural Therapy with Gay and Lesbian and Bisexual Clients, Person-Centred Therapy with Gay and Lesbian and Bisexual Clients, Psychoanalytic Therapy with Gay and Lesbian and Bisexual Clients, Therapists' Competencies for Counselling Gay and Lesbian and Bisexual Clients, The Importance of Therapists' Sexual Orientation, when Counselling Gay and Lesbian and Bisexual Clents, Rationale for the Current Study, Aims, Research Questions, Hypotheses, Method, Design, Participant, Sampling Criteria, Materials, Procedure, Ethics, Analytic Strategy, Results, Descriptive Statistics, Results Description, Dicussion, Summary of Findings, Overview of the Study, Limitations of the Research, Strengths of the Research, Conclusion, References, Appendices.